Pentingnya Sikap Transparansi Dalam Pengawasan Pendidikan - Shelty Deity Meity Sumual; Meytha Meyske Wongkar; Samuel Harry Mosey; Davison Pagawak (Departement of Mathematics Education, 2024)
Transparency is necessary in education supervision because it helps build trust and respect between supervisors and supervised stakeholders. When oversight is transparent, it will be clear to all stakeholders what expectations and standards are in place, what issues are being addressed or need to be addressed, and what decisions and actions are being taken. Education this time is often used as a business for a few power holders, thus giving birth to human resources who are immoral and have no morals. This transparency helps create a sense of fairness and integrity, increases trust in the system and provides a foundation for productive and successful oversight. The research method used is a qualitative approach with a literature study research method. The result of this study is that transparency is needed in terms of education supervision because it helps build trust and openness between stakeholders. This allows everyone to know what is happening in the education system and understand the actions taken. With transparency, stakeholders can be confident that decisions and policies are made and implemented fairly and effectively.